2006
DOI: 10.1111/j.1440-1746.2006.04190.x
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic effects of 10 mg/day rabeprazole administration on reflux esophagitis was not influenced by the CYP2C19 polymorphism

Abstract: The therapeutic effects of 10 mg/day RPZ administration on RE may be uninfluenced by the CYP2C19 polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
0
28
1
2
Order By: Relevance
“…Results of this meta-analysis were in line with another meta-analysis by Zhao et al [72], also documenting that patients with NM have lower odds of H. pylori eradication compared to IM and PM. The nonsignificant results for CYP2C19 effect on therapeutic outcomes of rabeprazole and esomeprazole in this meta-analysis and few other studies [71,73] can be explained by the lower contribution of CYP2C19 in esomeprazole and rabeprazole metabolism compared to other PPIs. Specifically, rabeprazole is predominantly metabolized via nonenzymatic clearance.…”
Section: Cyp2c19 and Ppi Pharmacogeneticscontrasting
confidence: 68%
See 2 more Smart Citations
“…Results of this meta-analysis were in line with another meta-analysis by Zhao et al [72], also documenting that patients with NM have lower odds of H. pylori eradication compared to IM and PM. The nonsignificant results for CYP2C19 effect on therapeutic outcomes of rabeprazole and esomeprazole in this meta-analysis and few other studies [71,73] can be explained by the lower contribution of CYP2C19 in esomeprazole and rabeprazole metabolism compared to other PPIs. Specifically, rabeprazole is predominantly metabolized via nonenzymatic clearance.…”
Section: Cyp2c19 and Ppi Pharmacogeneticscontrasting
confidence: 68%
“…While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80]. Nonetheless, other studies suggest CYP2C19 is important for all PPIs.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, rabeprazole offers rapid effects against gastroesophageal reflux disease. Furthermore, rabeprazole is considered safer than omeprazole or lansoprazole, because the effects of rabeprazole against gastroesophageal reflux disease are not influenced by CYP2C19 polymorphism (9). Many cases of collagenous colitis in hemodialysis patients have been attributed to lansoprazole.…”
Section: Case Descriptionmentioning
confidence: 99%
“…4%) excessive esophageal acid exposure. Endoscopic healing can be achieved in 90 100 and 80 85% of patients with mild and severe reflux esophagitis, respectively, by standarddose oral PPI therapy, which is the first-line treatment for GERD 2,3 . However, according to a report in 2015, the endoscopic healing rate by PPI (primarily standard-dose PPI) therapy decreased to about 70 and 60% in grade C and grade D reflux esophagitis, respectively, based on the LA classification, and the prevalence of severe reflux esophagitis that cannot be healed with standard-dose PPI is increasing 4 .…”
Section: Introductionmentioning
confidence: 99%